شبكة المحطات المناخية في شمال-غرب ليبيا ودورها في رصد التغير المناخي (Comprehensive Journal of Science, 2025)
This research aimed to identify the attitudes of students at the Faculty of Education, Yefren, Zintan University, towards their professors, according to the gender variable (male or female). The sample size was (100) research items, drawn randomly. The research instrument used was a test developed by Al-Kubaisi, designed to measure students' attitudes towards their professors.The research reached the following Results:1-      1-It was found that students have a positive attitude towards their professors2-      The results showed that the attitude is not affected by the gender variable (male or female).3-      The results revealed statistically significant differences in attitudes towards       professors, perhaps That is Returns to males having more freedom and a stronger relationship with professors, and according to the Habits of the community.